Titanium-Alloy Anchoring System as a Suitable Method of Extracapsular Repair - Dominic, Christopher; Lanz, Otto I.; Muro, Noelle; Sawyere, Dominique; Aulakh, Karanvir; Pancotto, Theresa; Seda, David (Frontiers in Veterinary Science, 2020)
Objective: To characterize the effect of a titanium-alloy anchoring system (TAS) on the motion of the cranial cruciate ligament (CrCL) deficient stifle. To compare the motion with the TAS to that of the CrCL-intact and CrCL-deficient stifle. Study Design: Each canine pelvic limb was mounted in a loading jig under 30% body weight. Motion data was collected using an electromagnetic tracking system at stifle angles of 125o, 135o and 145o with the CrCL-intact, CrCL-deficient and the TAS applied. Results: Total translation of the CrCL-deficient stifle following the TAS was reduced, but remained greater than the CrCL-intact stifle at angles of 125o, 135o, and 145o. Internal rotation of the TAS groups was greater than the CrCL-intact group at 145o, but not 125o and 135o. Varus motion of the TAS group was decreased compared to the CrCL-deficient group, but increased compared to the CrCL-intact group at angles of 125o, 135o. and 145o. Conclusion: Total translation and internal rotation of the CrCL-deficient stifle following the TAS differed from that of the CrCL-intact stifle. However, the TAS reduced total translation and internal rotation of the tibia relative to the femur in the CrCL-deficient stifle to levels that may yield clinically acceptable results.